Climate change adaptation in Bangladesh: Current practices, challenges and the way forward - Md. Arif Chowdhury; Md. Khalid Hasan; Syed Labib Ul Islam (Elsevier, 2022)
Geographical location and socioeconomic dynamics have increased the vulnerabilities of the people of Bangladesh to the impacts of climate change. Effective adaptation practices would reduce the adverse effects on livelihood, health, agriculture, and the environment- particularly in the coastal areas. To cope with climate change impacts, diverse scientific and indigenous knowledge is being utilized. Nevertheless, various barriers are hindering sustainable adaptation. This review focuses on identifying the existing and likely adaptation strategies as well as the barriers to coping with the impacts of climate change in Bangladesh. Due to the increasing frequency and intensity of disasters, many people are being displaced towards urban settings, where natural and man-made challenges are hampering sustainable adaptation. A lack of in-depth knowledge about the vulnerabilities, overlooking the needs of local communities, and inadequate integration of policies and programs have also been identified as challenges to climate change adaptation.